1998
DOI: 10.1074/jbc.273.47.31283
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Sites Involved in Ligand Association and Dissociation at the Extracellular Domain of the Kinase Insert Domain-containing Receptor for Vascular Endothelial Growth Factor

Abstract: The kinase insert domain-containing receptor (KDR) for vascular endothelial growth factor (VEGF) has been shown to be involved in vasculogenesis and angiogenesis. This receptor is characterized by seven immunoglobulin (Ig)-like domains within its extracellular region. To identify the domains involved in VEGF binding, we constructed various deletion mutants of the extracellular region fused with the crystallizable fragment portion of an IgG and then examined the binding affinity with VEGF by means of the BIAcor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 26 publications
6
88
1
4
Order By: Relevance
“…We also showed that the 4th to 7th Ig regions are essential for the receptor dimerization (Tanaka et al, 1997;Shinkai et al, 1998).…”
Section: Structure Of Vegf Receptorsmentioning
confidence: 92%
“…We also showed that the 4th to 7th Ig regions are essential for the receptor dimerization (Tanaka et al, 1997;Shinkai et al, 1998).…”
Section: Structure Of Vegf Receptorsmentioning
confidence: 92%
“…A previous binding study indicated that both D4 and D5 increase the affinity of VEGFR-2 for VEGF-A. Compared with D1-3, D1-5 showed 86-fold greater affinity and D1-4 showed 16-fold greater affinity (34). Similarly, both D4 and D4-5 of VEGFR-1 have been shown to enhance ligand-induced receptor dimerization in cross-linking experiments (35).…”
Section: Discussionmentioning
confidence: 99%
“…KDR 7N carrying the N-terminal 1st to 7th Ig-like domains and KDR 5 d 1N carrying the 2nd to 5th Ig-like domains of KDR fused with the Fc portion of an IgG (KDR 7N-Fc and KDR 5 d 1N-Fc, respectively) were obtained as described previously (Shinkai et al, 1998). The production of anti-human Flt-1 mAbs including KM1750 (mouse IgG2b) and anti-human KDR mAbs including KM1992 (mouse IgG1) will be described elsewhere (M Ito et al, in preparation).…”
Section: Anti-vegf Receptors Mabsmentioning
confidence: 99%